Elision of Consonants in Arabic: Regularity and Irregularity (المجلة الدولية للعلوم التربوية والآداب, 2025)
This paper analyzes phonological studies of elision in Arabic. Certain deletion cues are proposed to be articulatory effects that occur naturally and involuntarily during rapid speech. The linguistic phenomenon facilitates a reduction in the effort required for lengthy utterances. Elision, which can be defined as "omission" or "deletion," is a unique idea that appears when people change quickly, such as when letters or sounds are cut out. This phenomenon can be described as an example of economic efficiency. In addition to addressing the issue of energy conservation, it simplifies the process of expressing oneself verbally and in writing.The data presented herein are illustrated through various forms and examples intended for direct educational purposes. The information was gathered from reputable sources such as Google Scholar, Google Books, and other online platforms. This study addresses the phonological phenomenon of elision in classical Arabic, recognizing it as a linguistic event prevalent across diverse human societies. Through this research, the study seeks to explore the definition of the omission concept within the Arabic language, thereby illuminating several aspects of phonetics and phonology.